Развитие критического мышления студентов (из опыта организации дисциплины «Профессиональные ориентиры учителя») - Данилова, В.В. (My University, 2016)
This article deals with the features of formation of critical thinking of students of specialty 5B011900 "A foreign language: two foreign languages". Two aspects of the concept "critical thinking" are given in article. The author considers some methods of developing critical thinking in English. The author gives a conclusion about the need in parallel formation of critical thinking without exclusion of linguistic skills
Keywords: critical thinking; linguistic skill; INSERT reading; "6 W" technique; a method of focal objects